(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
This article explores the development and processes of government and nongovernmental preschool education and reveals theoretical scientific significance. Up to the end of the school year, the physical, moral, aesthetic, and physiological development of the educational organization will be achieved